Evaluation of two delirium screening tools for detecting post-operative delirium in the elderly - Neufeld, K. J. (Oxford University Press, 2013)
BACKGROUND: Postoperative delirium in the elderly is common and associated with poor outcomes, but often goes unrecognized. Delirium screening tools, validated in postoperative settings are lacking. This study compares two screening tools [Confusion Assessment Method for the Intensive Care Unit (CAM-ICU) and Nursing Delirium Symptom Checklist (NuDESC)] with a DSM-IV-based diagnosis of delirium, conducted by neuropsychiatric examination in postoperative settings. METHODS: Consecutive English-speaking patients, ≥70 yr, undergoing surgery with general anaesthesia and capable of providing informed consent, were recruited. Diagnostic test characteristics were compared for each screening tool vs neuropsychiatric examination, both in the Post-Anaesthesia Care Unit (PACU), and daily during inpatient hospitalization, adjusting for repeated measures. RESULTS: Neuropsychiatric examination identified delirium in 45% of 91 patients evaluated in the PACU and in 32% of 166 subsequent delirium assessments on the ward in the 58 admitted patients. The sensitivity [95% confidence interval (CI)] of delirium detection of the CAM-ICU in the PACU, and in all repeated assessments was 28% (16–45%) and 28% (17–42%), respectively; for the NuDESC (scoring threshold ≥2), 32% (19–48%) and 29% (19–42%), respectively, and the NuDESC (threshold ≥1), 80% (65–91%) and 72% (60–82%), respectively. Specificity was >90% for both the CAM-ICU and the NuDESC (threshold ≥2); specificity for the NuDESC (threshold ≥1), in the PACU was 69% (54–80%) and 80% (73–85%) for all assessments. CONCLUSIONS: While highly specific, neither CAM-ICU nor NuDESC (threshold ≥2) are adequately sensitive to identify delirium post-operatively; NuDESC (threshold ≥1) increases sensitivity, but reduces specificity.